Transcription termination between polo and snap, two closely spaced tandem genes of D. melanogaster - Tan-Wong, S; Proudfoot, N; Tian, B; Carmo, A; Ji, Z; Henriques, T; Moreira, A (Taylor and Francis, 2012)
Transcription termination of RNA polymerase II between closely spaced genes is an important, though poorly understood, mechanism. This is true, in particular, in the Drosophila genome, where approximately 52% of tandem genes are separated by less than 1 kb. We show that a set of Drosophila tandem genes has a negative correlation of gene expression and display several molecular marks indicative of promoter pausing. We find that an intergenic spacing of 168 bp is sufficient for efficient transcription termination between the polo-snap tandem gene pair, by a mechanism that is independent of Pcf11 and Xrn2. In contrast, analysis of a tandem gene pair containing a longer intergenic region reveals that termination occurs farther downstream of the poly(A) signal and is, in this case, dependent on Pcf11 and Xrn2. For polo-snap, displacement of poised polymerase from the snap promoter by depletion of the initiation factor TFIIB results in an increase of polo transcriptional read-through. This suggests that poised polymerase is necessary for transcription termination. Interestingly, we observe that polo forms a TFIIB dependent gene loop between its promoter and terminator regions. Furthermore, in a plasmid containing the polo-snap locus, deletion of the polo promoter causes an increase in snap expression, as does deletion of polo poly(A) signals. Taken together, our results indicate that polo forms a gene loop and polo transcription termination occurs by an Xrn2 and Pcf11 independent mechanism that requires TFIIB.